Synthesis, Chacterization, and Thermal Study of Terpolymeric Resin Derived from m-cresol, Hexamine and Formaldehyde - K. M. Khedkar; V. V. Hiwase; A. B. Kalambe; S. D. Deosarkar (E-Journal of Chemistry)
Terpolymeric resin was prepared from m-cresol (0.1M), hexamine (0.05M) and formaldehyde (0.2M) by acid catalyzed polycondensation method using 1M HCl in temperature range of 122-130°C.The resin was abbreviated as m-CHF-I. The molecular weight of terpolymer was determined by non-aqueous conductometric titration technique. The structure of resin was determined by its elemental analysis, UV-VIS, IR, and NMR data. The thermokinetic parameters were determined using Freeman-Carroll (FC) and Sharp Wentworth (SW) method in temperature range (410-485°C).The values of activation energies (Ea), entropy (∆S), and free energies (∆G) were in good agreement . The order of degradation reaction determined by FC method was confirmed by SW method.